Preparation, application, regeneration and recovery method of Ni-doped defect WS2 catalyst
The preparation of Ni doped defective WS2 catalysts by one-step hydrothermal method has solved the problems of poor stability of existing catalysts and difficulty in handling waste catalysts, and achieved efficient hydrodesulfurization and resource utilization of waste catalysts.
Patent Information
- Application Number
- CN202411988508.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing hydrodesulfurization catalysts have problems such as high reaction temperature and poor stability, which are difficult to apply on a large scale in industry, and waste catalysts are harmful to the environment.
A one-step hydrothermal method is used to prepare Ni doped defective WS2 catalyst, and Ni3S2 is generated by high-temperature and high-pressure reaction of nickel salt and vulcanizing agent, and WS2 is generated by adsorption of organic species, and defect-rich structure is formed to enhance the activity and stability of the catalyst.
A catalyst with high activity and high stability has been achieved. The catalyst's hydrogenation conversion rate of organic sulfur in coal gas reaches 98% to 100%, and its stability is greater than 60 hours. The regeneration efficiency is improved through hydrogen reduction and regeneration, and the resource utilization of waste catalysts is realized.
Smart Images

Figure CN119793491A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of environmental protection and resource recycling, and more specifically to a method for preparing a Ni-doped defective WS2 catalyst and using it for hydrodesulfurization, as well as a method for recycling and recovering the catalyst. Background Art
[0002] Blast furnace gas is a byproduct produced during the ironmaking process, and its main components include CO, CO2, H2, CH4, N2 and sulfur-containing pollutants. The combustible gases such as CO and H2 in blast furnace gas have high recovery value. In order to recover the combustible gases in blast furnace gas, it is necessary to dedust and desulfurize the blast furnace gas. Hydrogenation conversion desulfurization (HDS) technology is a widely used organic sulfur removal method, which can meet the requirements of blast furnace gas desulfurization accuracy. The method has high conversion efficiency for organic sulfur, few by-products, a wide temperature range, and can directly use hydrogen in the gas for desulfurization, which can achieve deep purification of blast furnace gas. CN103627425A discloses a method for hydrodesulfurization of oil residues, which immerses nickel salt or cobalt salt talc into a sodium salt solution, and obtains a catalyst with a high dispersion of loaded metal after heat treatment, which has high desulfurization activity. However, a large amount of sodium element is introduced into the catalyst, which destroys the surface properties of the catalyst and affects the stability of the catalyst. At present, hydrodesulfurization catalysts have problems such as high reaction temperature and poor stability, which makes it difficult to apply them on a large scale in industry. Therefore, the preparation of highly active and highly stable catalysts is of great significance for achieving the precise removal of organic sulfur in coal gas.
[0003] my country has abundant tungsten resources and high output. Tungsten materials are widely used in aerospace, military industry, advanced manufacturing and other fields due to their excellent properties such as high melting point, high strength and good thermal conductivity. Tungsten sulfide is a two-dimensional transition metal dichalcogenide (2D TMDs) with a unique layered structure, good cracking performance, high catalytic activity, reliable stability and long service life. It has great application potential in research fields such as optics, electricity, tribology, hydrogen evolution performance, sodium storage, photocatalysis, and thermal catalysis. It is often used as a petroleum catalyst, hydrodesulfurization catalyst, fuel manufacturing, anode of organic electrolyte rechargeable batteries, and nano-ceramic composite materials. The methods for preparing tungsten disulfide include mechanical exfoliation, electrochemical lithium ion intercalation, liquid phase exfoliation, chemical vapor precipitation and hydrothermal method. Among them, the hydrothermal method has mild reaction conditions and strong operability. By changing the hydrothermal reaction conditions (hydrothermal temperature, hydrothermal time, ratio, etc.), the size and morphology of WS2 can be effectively controlled. CN111036276A discloses a tungsten-based presulfurization-free hydrotalcite hydrodesulfurization catalyst and a preparation method thereof. The tungsten-based presulfurization-free hydrotalcite hydrodesulfurization catalyst is obtained by introducing thiotungstate anions into the interlayer of nickel-aluminum hydrotalcite and then activating it with nitrogen at high temperature. The catalyst achieves high dispersion and high loading of active metal components, and exhibits high hydrodesulfurization activity in the hydrodesulfurization reaction of oil products.
[0004] Catalysts are crucial to the development of modern industry. In chemical industry production, 60% to 80% of chemical reactions require corresponding catalysts. In the field of environmental protection fine desulfurization and crude oil refining, a large amount of waste hydrodesulfurization catalysts will be generated. Because it contains crude oil and heavy metals, it is harmful to the environment, so it is listed as hazardous waste by my country's Ministry of Environmental Protection. The valuable metals in the waste hydrodesulfurization catalyst are high-quality secondary resources. Recycling them can not only alleviate the problem of resource shortage, but also protect the environment. CN116732319A discloses a method for resource utilization of waste hydrodesulfurization catalysts. The waste hydrodesulfurization catalysts (including aluminum oxide, molybdenum oxide, cobalt oxide, phosphorus oxide) come from a cracking gasoline device. High-purity Mo and Co products are obtained by alkali solution impregnation, solid-liquid separation, adding Mo and Co precipitants, etc. The remaining slag can be used to prepare aluminum oxide, realizing the high added value utilization of all elements. Therefore, the waste hydrodesulfurization catalyst is recycled and utilized, which can not only prevent the loss and waste of valuable metals (W, Ni), but also alleviate resource shortages and reduce its pollution to the environment, which has important environmental and economic benefits.
[0005] Therefore, how to develop a coal gas deep hydrodesulfurization catalyst and provide a resource utilization idea for waste hydrodesulfurization catalyst are problems that technical personnel in this field need to solve urgently. Summary of the invention
[0006] In view of this, the present invention provides a method for the preparation, application, regeneration and recovery of a Ni-doped defective WS2 catalyst. The Ni-doped defective WS2 nanosheet catalyst is prepared by a one-step hydrothermal method. The metal components of the prepared catalyst react appropriately with the carrier and have high hydrodesulfurization activity and stability. The catalyst with reduced desulfurization efficiency is regenerated by hydrogenation reduction, and the valuable metals in the waste hydrodesulfurization catalyst are utilized as resources.
[0007] One of the purposes of the present invention is to provide a method for preparing a Ni-doped defective WS2 catalyst, comprising the following steps:
[0008] S11. The molecular sieve, nickel salt, tungstate, sulfiding agent, inorganic hydroxylamine hydrochloride and organic modifier are dissolved in deionized water, a certain amount of organic acid is added, and the mixture is transferred into a polytetrafluoroethylene reactor for a hydrothermal reaction for a certain period of time;
[0009] S12. After the reaction is completed, the product is naturally cooled to room temperature, filtered, washed with deionized water and anhydrous ethanol several times, and dried in an oven at 80 to 120 ° C for 8 to 16 hours to obtain a solid product;
[0010] S13. The solid product is passed through a 40-60 mesh sieve, placed in a photothermal catalytic reactor, and reduced with 2%-10% H2 at 300°C-350°C to obtain a Ni-doped defective WS2 catalyst.
[0011] Preferably, in S11, the molecular sieve is selected from ZSM-5, SBA-15, KIT-6, and MCM-41, the nickel salt is selected from nickel nitrate, nickel sulfate, and nickel hydroxide, the tungstate is selected from ammonium metatungstate and sodium tungstate, the vulcanizing agent is selected from thiourea and thioacetamide, the inorganic hydroxylamine hydrochloride is selected from hydroxylamine hydrochloride and N,O-dimethylhydroxylamine hydrochloride, the organic modifier is selected from hexadecyltrimethylammonium bromide and ascorbic acid, and the organic acid is selected from formic acid, acetic acid, sulfuric acid, and phosphoric acid.
[0012] Preferably, the mass ratio of molecular sieve, nickel salt, tungstate, sulfiding agent, inorganic hydroxylamine hydrochloride, and organic modifier is (0.1-1):(1-2):(1-2):(1-2):(1-2):(1-2):(1-2);
[0013] The solid-liquid ratio of the molecular sieve to deionized water is 1 / 200 to 1 / 50, and the solid-liquid ratio of the molecular sieve to the organic acid is 0.0082 to 0.0273.
[0014] Preferably, in S11, the temperature of the hydrothermal reaction is 160° C. to 240° C., and the time is 7 h to 24 h.
[0015] The inventive concept using the above technical solution is:
[0016] 1. Nickel salt and sulfiding agent will generate Ni3S2 in a reactor at 220℃ under high temperature and high pressure environment, providing sulfur vacancies for hydrogenation and removal of organic sulfur.
[0017] 2. Tungstate and sulfiding agent generate WS2 in a reactor at 220℃ under high temperature and high pressure environment, providing more active sites for hydrogenation desulfurization.
[0018] 3. The hydrothermal method introduces organic species (including organic hydroxy acids or hydroxy salts and organic sulfiding agents). During the reaction, the organic species will be adsorbed on the surface of sulfide ions in large quantities, partially restricting the growth of sulfide crystals, forming a defect-rich structure, and providing more defect sites, thereby improving the activity of the catalyst.
[0019] The second object of the present invention is to provide an application of a Ni-doped defective WS2 catalyst, comprising the following steps:
[0020] In the photothermal catalytic reactor, a certain amount of Ni-doped defective WS2 catalyst was taken, the flow rate was 200 mL / min, and the reaction space velocity was 30000-40000 h -1 , blast furnace gas with ultraviolet light intensity of 7 to 10W, using catalyst to carry out photothermal synergistic hydrogenation conversion of organic sulfur at 120℃~200℃, converting the difficult-to-remove organic sulfur into easily-removable inorganic sulfur (H2S), and then purifying it through adsorption column filled with fine desulfurization catalyst to complete the fine removal of H2S.
[0021] The beneficial effects of adopting the above technical solution are: the hydrogenation conversion rate of organic sulfur in coal gas by the Ni-doped defective WS2 catalyst reaches 98% to 100%, and the catalyst stability is greater than 60h.
[0022] Preferably, the fine desulfurization catalyst is selected from various combinations of zinc salts, iron oxide, molecular sieves, activated carbon and bismuth vanadium.
[0023] Preferably, the Ni-doped defective WS2 catalyst is 0.2 g.
[0024] Furthermore, the present invention provides a method for preparing a fine desulfurization catalyst, the specific steps of which are as follows:
[0025] (1) dissolving a zinc salt in a mixed solution of an organic alcohol having a volume ratio of 20% to 60% to obtain a zinc-containing solution;
[0026] The molecular sieve and anhydrous ethanol are mixed in a molar ratio of 1:1 to 1:4 to prepare a molecular sieve sol. During the mixing and stirring, distilled water and an inorganic acid are added dropwise to ensure that the molar ratio of the molecular sieve: distilled water: inorganic acid is 1:1:0.1 to 1:2:0.5;
[0027] A zinc-containing solution is mixed with a molecular sieve sol to obtain a precursor solution, wherein the molar ratio of zinc to the molecular sieve is 1:1 to 1:2.
[0028] (2) The precursor solution is placed in an oven at 80°C to 120°C and dried for 12 to 24 hours to obtain a precursor.
[0029] (3) After drying and grinding the precursor, place it in a muffle furnace at 200℃~400℃ and bake it for 2~6h.
[0030] (4) The tablets were passed through a 40-60 mesh sieve and 0.2-0.5 g was filled into a glass reaction tube with an inner diameter of 8 mm to obtain a refined desulfurization catalyst.
[0031] Furthermore, the working conditions of the fine desulfurization catalyst are: H2 content of 4% to 10%, gas velocity of 15 to 30 mL / min, and adsorption temperature of 20°C to 100°C.
[0032] Preferably, the zinc salt is selected from zinc oxide, zinc nitrate, zinc sulfate, and zinc carbonate;
[0033] The organic alcohol mixture is selected from two of methanol, ethylene glycol and propylene glycol, and the mixing volume ratio is 1:1 to 1:2;
[0034] The solid-to-liquid ratio of the zinc salt and organic alcohol mixture is 0.02 to 0.1;
[0035] Molecular selection was from ZSM-5, SBA-15, KIT-6, MCM-41;
[0036] The inorganic acid is selected from hydrochloric acid, sulfuric acid and phosphoric acid.
[0037] The third object of the present invention is to provide a cyclic regeneration method of a Ni-doped defective WS2 catalyst, the specific steps of which are:
[0038] The Ni-doped defective WS2 catalyst with reduced desulfurization efficiency is regenerated under a high-temperature and high-pressure hydrogen atmosphere, and the number of regeneration cycles is ≥2.
[0039] Preferably, the regeneration conditions are to introduce 2% to 5% hydrogen at 320°C to 470°C, 1.6 to 9.8 MPa and a flow rate of 20 to 80 mL / min, using N2 as the protective gas, and complete the regeneration after 12 to 36 hours.
[0040] The beneficial effect of adopting the above technical solution is that the catalyst with reduced desulfurization efficiency has a regeneration efficiency of more than 98%, and generally has the most economic value after 2 to 5 hydrogen reduction regenerations.
[0041] The fourth object of the present invention is to provide a method for resource utilization of waste hydrodesulfurization catalyst, the specific steps of which are as follows:
[0042] S21. The spent hydrodesulfurization catalyst is calcined in an air atmosphere at 500°C to 800°C for 3h to 6h;
[0043] S22. Take an aqueous solution of an inorganic acid having a concentration of 0.1 mol / L to 3.0 mol / L, and ultrasonically immerse the spent hydrodesulfurization catalyst at a solid-liquid ratio of 15:1 to 10:1 at 50°C to 100°C for 30 to 60 minutes, filter and separate the residue and the filtrate, and the leaching rate of valuable metals is greater than 98%;
[0044] S23. Add a quaternary ammonium salt aqueous solution with a concentration of 0.5 mol / L to 2.0 mol / L to the filtrate, add kerosene with a volume of 60% to 65% of the total reaction solution as a diluent, add 5% to 7.5% of n-decanol with a volume of 5% to 7.5% of the total reaction solution as a modifier, and the ratio of the aqueous phase to the organic phase is 1:1 to 1:2 to obtain a tungsten-containing extract (oil phase) and a nickel-containing extract (oil phase), and the extraction rates of tungsten and nickel are both greater than 98%;
[0045] S24. Adding NH4OH or NaOH aqueous solution to the tungsten-containing extract, stirring on an electromagnetic stirrer at 80°C to 100°C until dry to obtain an ammonium tungstate or sodium tungstate compound having a purity greater than 99%;
[0046] H2C2O4 or H2SO4 or HCl is added as a precipitant to the nickel-containing extract, and precipitation recovery is performed in an environment of 40°C to 60°C to obtain nickel oxalate, nickel sulfate or nickel chloride with a purity greater than 98%.
[0047] Preferably, the inorganic acid is selected from sulfuric acid, hydrochloric acid, and nitric acid; the quaternary ammonium salt is selected from ammonium hydroxide or methyl trioctyl ammonium chloride; and the kerosene is analytically pure and selected from No. 200 solvent oil with a purity of 99.99% or No. 260 solvent oil with a purity of 99%.
[0048] Preferably, in step S24, the concentration of the NH4OH or NaOH aqueous solution is 0.1 mol / L to 1.0 mol / L, and the molar ratio of hydroxide to tungstate ion is 1:1 to 1:3;
[0049] The concentration of H2C2O4 or H2SO4 or HCl solution is 0.1 mol / L to 1.0 mol / L, the molar ratio of oxalate to nickel ion is 1:1 to 1:2, the molar ratio of sulfate to nickel ion is 1:1 to 1:3, and the molar ratio of chloride ion to nickel ion is 3:1 to 2:1.
[0050] The fifth object of the present invention is to provide a Ni-doped defective WS2 catalyst, which is doped on a spherical catalyst stacked with multiple layers of flaky WS2 by a one-step hydrothermal method using Ni as an active component and is used in a coal gas hydrodesulfurization process.
[0051] Compared with the prior art, the catalyst developed by the present invention converts organic sulfur gases such as COS, CS2, and CH3SH into H2S at 200°C through the synergistic conversion of light and heat. The conversion rate of organic sulfur is close to 100%, and the H2S selectivity is greater than 99%. For catalysts with reduced desulfurization efficiency, after hydrogen reduction and regeneration, the regeneration efficiency is greater than 98%, and they can be recycled 3 to 5 times. The catalyst that fails after recycling is the waste hydrodesulfurization catalyst. Finally, the valuable metals (W, Ni) in the waste hydrodesulfurization catalyst are recycled using the full process flow of pretreatment-leaching-extraction-strip extraction-productization.
[0052] It can be seen from the above technical solution that, compared with the prior art, the beneficial effects achieved by the present invention are:
[0053] 1. The present invention discloses a method for preparing a Ni-doped defective WS2 catalyst and using it for hydrodesulfurization. Through the photothermal synergistic conversion of organic sulfur in coal gas, the corrosion of corrosive chemicals on back-end equipment and transportation pipelines can be reduced, thereby extending the service life and operating efficiency of the equipment.
[0054] 2. The present invention adopts a hydrothermal method to introduce organic species (including organic hydroxy acids or hydroxy salts and organic sulfiding agents). During the reaction, the organic species will be adsorbed on the surface of sulfide ions in large quantities, partially restricting the growth of sulfide crystals, forming a defect-rich structure, and providing more defect sites, thereby improving the activity of the catalyst.
[0055] 3. Preparation method of catalyst: Organic hydroxy acid or hydroxy salt is used as an auxiliary agent to form a complex with metal ions, so that nickel and tungsten are sulfided at the same time, so that the catalyst is evenly distributed on the carrier. The presence of nickel has a significant improvement in hydrodesulfurization activity, and the catalytic performance is improved by more than 30%.
[0056] 4. The spherical WS2 formed by stacking sheets at a hydrothermal temperature of 220°C can not only maintain a complete structure, but also partially collapse the ZSM-5 molecular sieve framework. The doped Ni will interact with the Al element in the ZSM-5 molecular sieve framework, which is beneficial to the hydrogenation conversion and removal of organic sulfur. After the MCM-41, KIT-6, and SBA-15 molecular sieves are modified by metal ions, the hydrothermal stability will be significantly improved, thereby maintaining good framework stability under hydrothermal conditions of 220°C.
[0057] 5. The catalyst material preparation method of the present invention is simple and easy to industrialize. The catalyst with reduced desulfurization efficiency can be regenerated by hydrogen reduction, which has great economic and environmental benefits.
[0058] 6. Resource utilization of spent hydrodesulfurization catalysts can prevent the loss and waste of valuable metals (W, Ni) and reduce their pollution to the environment, which has important environmental and economic significance. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0060] Figure 1 XRD patterns of catalysts synthesized at different hydrothermal temperatures with or without Ni doping on the catalyst support.
[0061] Figure 2 The XPS spectra of catalysts synthesized at different hydrothermal temperatures with or without Ni doping on the catalyst support.
[0062] Figure 3 The SEM spectra of the catalysts synthesized at different hydrothermal temperatures with or without Ni doping on the catalyst support: (ab) SEM spectrum of WS2 / Ni-ZSM-5 (160°C); (cd) SEM spectrum of WS2 / Ni-ZSM-5 (220°C); (ef) SEM spectrum of WS2 / Ni-ZSM-5 (240°C); (gh) SEM spectrum of WS2 / ZSM-5 (220°C).
[0063] Figure 4 TEM spectra of the catalysts synthesized at different hydrothermal temperatures with or without Ni doping on the carrier and after Ni doping: (ab) TEM spectrum of WS2 / Ni-ZSM-5 (160°C); (cd) SEM spectrum of WS2 / Ni-ZSM-5 (220°C); (ef) TEM spectrum of WS2 / Ni-ZSM-5 (240°C); (gh) TEM spectrum of WS2 / ZSM-5 (220°C). DETAILED DESCRIPTION
[0064] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0065] The raw materials used to prepare Ni-doped defective WS2 catalyst are:
[0066] 1) Molecular sieve: It is a synthetic zeolite molecular sieve with a high silicon-aluminum ratio, with unique structure and performance. ZSM-5 molecular sieve has a three-dimensional channel structure, and its pore system is complex and interconnected. This structure gives it good diffusion performance. ZSM-5 molecular sieve has strong acidity and high acid content, has B acid and L acid sites, has a larger specific surface area, good structural stability, and an adjustable silicon-aluminum ratio. The catalyst effect is good and is conducive to the dispersion of metal components. In addition, the effective shape, size and curvature of the pores of the ZSM-5 molecular sieve prevent the formation and accumulation of large condensation products, and limit the formation of large condensation molecules from side reactions, so that the ZSM-5 catalyst is not easy to deposit carbon.
[0067] 2) Nickel salt: Ni doping in the supported WS2 catalyst method can produce more active sites, large specific surface area and effective pores in the hydrothermal one-step method, which is conducive to the diffusion of the catalyst and improves the catalytic desulfurization efficiency of the catalyst; although WS2 has a large specific surface area, the electron mobility of WS2 is low, and Ni doping can improve the electron mobility of the catalyst, promote charge transfer, adjust the electronic structure and adsorption free energy, so as to optimize the desulfurization performance of the catalyst. Ni doping is conducive to the formation of multi-layered WS2 or MoS2 stacked in sheets, increasing the active sites of the catalyst, improving the stability of the catalyst, and avoiding the formation of strong WO-Al bonds and inactive NiAl2O4 spinel through the relationship between the carrier, thereby improving the activity and selectivity of the catalyst.
[0068] 3) Tungstate: As a precursor for the synthesis of loaded WS2-type catalysts, it has excellent catalytic performance, thermal stability and certain electrophilic oxygen vacancies. Under acidic conditions (organic acid added during the hydrothermal reaction), it can enhance the catalytic activity of WS2-type catalysts. The formed WS2-WO3 complex has a high light response, which is beneficial to photocatalytic desulfurization.
[0069] 4) Sulfiding agent: It plays an important role in the synthesis of supported WS2 type catalysts, helping to form the best sulfide interface between different sulfides (Ni3S2 and WS2), changing the electronic structure, and increasing the active surface area of WS2. The use of sulfiding agent helps to maintain the long-term stable bending effect of WS2 nanosheets in an acid environment (organic acid added during the hydrothermal reaction), improve the stability of the catalyst, and form surface defects by doping Ni, which can improve the catalytic activity.
[0070] 5) Inorganic hydroxylamine hydrochloride: It is mainly used as a reducing agent in this experiment, affecting the oxidation state and electronic structure of the catalyst, which is beneficial to the synthesis of WS2-WO3 composite materials.
[0071] 6) Organic modifiers: They can enhance the activity and selectivity of catalysts by changing the surface properties and electronic structure of catalysts, improve the interaction between metal and support and the physicochemical properties of catalysts, and promote the removal of organic sulfur by photothermal synergistic hydrogenation.
[0072] Example 1 A method for preparing a Ni-doped defective WS2 catalyst:
[0073] 0.5g ZSM-5, 1.1g (NH4)6H2W 12 O 40 xH2O, 1.0gH2NCSNH2, 1.0gCTAB, 1.0ghydroxylamine hydrochloride were dissolved in 35mL deionized water, and 20mL formic acid was added. After magnetic stirring for 30min at room temperature, the mixture was transferred to a 100mL polytetrafluoroethylene reactor and hydrothermaled at 220℃ for 18h.
[0074] 0.5g ZSM-5, 1.0g Ni(NO3)2·6H2O, 1.1g (NH4)6H2W 12 O 40 xH2O, 1.0gH2NCSNH2, 1.0gCTAB, and 1.0ghydroxylamine hydrochloride were dissolved in 35mL deionized water, and 20mL formic acid was added. After magnetic stirring at room temperature for 30min, the mixture was transferred to a 100mL polytetrafluoroethylene reactor and hydroheated at 160℃, 220℃, and 240℃ for 18h, respectively.
[0075] The catalyst was naturally cooled to room temperature and then filtered, washed with anhydrous ethanol and deionized water for multiple times, and the obtained solid was dried in an oven at 70° C. for 12 h to obtain a black powder.
[0076] The black powder was pressed into tablets and passed through a 40-60 mesh sieve. 0.2 g of the sieved black catalyst was placed in a photothermal catalytic reactor and calcined at 320°C in a 5% H2 / N2 atmosphere for 12 h. The mixture was cooled to room temperature to synthesize WS2 / ZSM-5, WS2 / Ni-ZSM-5 (160°C), WS2 / Ni-ZSM-5 (220°C) and WS2 / Ni-ZSM-5 (240°C).
[0077] 5% H2, 30ppm CS2, and N2 were used as carrier gases to simulate blast furnace gas. The total flow rate was controlled at 200mL / min and the reaction space velocity was 40000h -1 , the ultraviolet light intensity is 9W, the relative humidity is 6.5%, 0.2g of the prepared catalyst material is placed in a photothermal catalytic reactor, and the catalyst is used to synergistically convert CS2 in blast furnace gas by photothermal reaction.
[0078] Catalyst performance tested at 200°C:
[0079] The CS2 conversion rate of WS2 / ZSM-5 catalyst was 40% under hot catalyst only, and 70% after adding UV light. The H2S selectivity was 50% under hot catalyst only, and 65% after adding UV light.
[0080] The CS2 conversion rate of WS2 / Ni-ZSM-5 (160°C) catalyst was 50% under hot catalyst only, and 70% after adding UV light. The H2S selectivity was 60% under hot catalyst only, and about 80% after adding UV light.
[0081] The WS2 / Ni-ZSM-5 (220°C) catalyst has a CS2 conversion rate of 70% only under hot catalyst and 100% after adding UV light. The H2S selectivity is 75% only under hot catalyst and greater than 99% after adding UV light.
[0082] The CS2 conversion rate of the WS2 / Ni-ZSM-5 (240°C) catalyst is 60% under hot catalyst only, and 80% after adding ultraviolet light. The H2S selectivity is 65% under hot catalyst only, and 85% after adding ultraviolet light.
[0083] Example 2
[0084] The H2S generated by the tail gas is adsorbed by the adsorption column filled with adsorbent to achieve the purification standard. The preparation method and adsorption conditions of the adsorbent are as follows:
[0085] Zinc nitrate is dissolved in a mixture of organic alcohol methanol and ethylene glycol (volume ratio of 30%) to obtain a zinc nitrate solution; molecular sieve ZSM-5 and anhydrous ethanol are mixed in a molar ratio of 1:4 to prepare a molecular sieve sol. During mixing and stirring, distilled water and inorganic acid sulfuric acid are added dropwise to ensure that the molar ratio of molecular sieve: water: hydrochloric acid is 1:2:0.5. The zinc nitrate solution is mixed with the ZSM-5 molecular sieve sol to obtain a precursor solution, in which the molar ratio of zinc to molecular sieve is 1:2. The precursor solution is placed in an oven at 110°C and dried for 24 hours. After drying and grinding, it is placed in a muffle furnace at 250°C and roasted for 4 hours. The tablet is passed through a 40-60 mesh sieve and 0.2g is filled in a glass reaction tube with an inner diameter of 8mm. The H2 content is 5%, the gas velocity is 20mL / min, and the desulfurization rate is 100% when the adsorption temperature is 80°C.
[0086] Example 3 A cyclic regeneration method of Ni-doped defective WS2 catalyst:
[0087] Take 1.0g of WS2 / ZSM-5, WS2 / Ni-ZSM-5 (160℃), WS2 / Ni-ZSM-5 (220℃) and WS2 / Ni-ZSM-5 (240℃) catalysts with reduced desulfurization efficiency, dry them in an oven at 80℃ for 12h, press them into tablets and pass them through a 40-60 mesh sieve, weigh 0.2g of the sieved catalyst and place it in a photothermal catalytic reactor, pass 5% H2 / N2 at a flow rate of 60mL / min, and pass it at 360℃ and 6MPa for 12h. Then, pass coal gas into the photothermal catalyst reactor, measure the content of various sulfur-containing substances by Foley chromatography, and calculate the content of WS2 / ZSM-5, WS2 / Ni-ZSM-5 (160℃), WS2 / Ni-ZSM-5 (220℃) and
[0088] The regeneration efficiencies of the four WS2 / Ni-ZSM-5 (240°C) catalysts were 70%, 80%, 98% and 85%, respectively. By comparing the performance of the catalyst materials with that of the first regeneration, the loss rates of the hydrogenation conversion desulfurization performance of the catalyst with decreased desulfurization efficiency were 5%, 3%, 2% and 2.8%, respectively, after each regeneration.
[0089] The above four catalysts are generally most economically valuable after being regenerated with hydrogen once, twice, four times and three times respectively.
[0090] Example 4 A method for recycling waste hydrodesulfurization catalyst:
[0091] 10.0g of spent hydrodesulfurization catalyst was placed in a muffle furnace and calcined in an air atmosphere at 650℃ for 4h for pretreatment. 2.0mol / L sulfuric acid was used, the solid-liquid ratio was 10:1, and ultrasonic immersion was performed at 80℃ for 60min. The leaching rate of valuable metals was greater than 98%. Then 1.5mol / L ammonium hydroxide was used, kerosene was used as a diluent, 6% n-decanol was added as a modifier, the ratio of liquid phase to organic phase was 1:1, and the extraction rates of tungsten and nickel were both greater than 98%. For the tungsten-containing extraction solution, 0.5 mol / L NH4OH (or NaOH) is added and stirred on an electromagnetic stirrer at 90°C until dry, and finally ammonium tungstate or sodium tungstate compounds with a purity greater than 99% are obtained; for the nickel-containing extraction solution, 0.45 mol / L H2C2O4 (or H2SO4, HCl) is added as a precipitant, the molar ratio of oxalic acid or sulfuric acid to nickel ions is 1:2, and precipitation recovery is carried out in an environment of 50°C, and finally nickel oxalate or nickel sulfate with a purity greater than 98% is obtained.
[0092] Example 5 A method for preparing a Ni-doped defective WS2 catalyst:
[0093] Combine 0.5gMCM-41, 1.0gNi(NO3)2·6H2O, 1.1g(NH4)6H2W 12 O40 xH2O, 1.0 g CH3CSNH2, 1.0 g ascorbic acid and 1.0 g hydroxylamine hydrochloride were dissolved in 35 mL deionized water, and then 20 mL acetic acid was added. After magnetic stirring at room temperature for 60 min, the mixture was transferred to a 100 mL polytetrafluoroethylene reactor and hydroheated at 220 °C for 18 h.
[0094] The catalyst was naturally cooled to room temperature and then filtered, washed with anhydrous ethanol and deionized water for multiple times, and the obtained solid was dried in an oven at 70° C. for 12 h to obtain a black powder.
[0095] The black powder was pressed into tablets and passed through a 40-60 mesh sieve. 0.2 g of the sieved black catalyst was placed in a photothermal catalytic reactor, calcined at 320° C. in a 5% H2 / N2 atmosphere for 12 h, and cooled to room temperature to synthesize WS2 / Ni-MCM-41.
[0096] The catalyst performance was tested at 200°C: the CS2 conversion rate of the WS2 / Ni-MCM-41 catalyst was 45% under only hot catalyst, and 60% after adding ultraviolet light. The H2S selectivity was 55% under only hot catalyst, and 70% after adding ultraviolet light.
[0097] Example 6 Preparation method of Ni-doped defective WS2 catalyst:
[0098] Combine 0.5gKIT-6, 1.0gNi(NO3)2·6H2O, 1.1g(NH4)6H2W 12 O 40 ·xH2O, 1.0gCH3CSNH2, 1.0gN,O-dimethylhydroxylamine hydrochloride and 1.0gCTAB were dissolved in 35mL deionized water, and then 20mL acetic acid was added. After magnetic stirring at room temperature for 60min, the mixture was moved to a 100mL polytetrafluoroethylene reactor and hydroheated at 220℃ for 18h. After naturally cooling to room temperature, the mixture was filtered and washed with anhydrous ethanol and deionized water for several times. The obtained solid was dried in an oven at 70℃ for 12h to synthesize WS2 / Ni-KIT-6.
[0099] The WS2 / Ni-KIT-6 catalyst was pressed into tablets and passed through a 40-60 mesh sieve. 0.2 g of the sieved catalyst was placed in a photothermal catalytic reactor and pre-sulfurized at 400°C in a 5% H2 / CS2 atmosphere for 4 hours. The catalyst was cooled to room temperature to synthesize WS2 / Ni-KIT-6. 5% H2, 30 ppm CS2, and N2 were used as carrier gases to simulate blast furnace gas. The total flow rate was controlled at 200 mL / min and the reaction space velocity was 40,000 h -1, the ultraviolet light intensity is 9W, the relative humidity is 6.5%, 0.2g of the prepared catalyst material is placed in a photothermal catalytic reactor, and the catalyst is used to synergistically convert CS2 in blast furnace gas by photothermal reaction.
[0100] The catalyst performance was tested at 200°C. The CS2 conversion rate of the WS2 / Ni-KIT-6 catalyst was 55% under only hot catalyst and 70% after adding ultraviolet light. The H2S selectivity was 60% under only hot catalyst and 75% after adding ultraviolet light.
[0101] Example 7 A method for preparing a Ni-doped defective WS2 catalyst:
[0102] 0.5g SBA-15, 1.0g Ni(NO3)2·6H2O, 1.1g (NH4) 10 H2(W2O7)6, 1.0gCH3CSNH2, 1.0gN,O-dimethylhydroxylamine hydrochloride and 1.0g ascorbic acid were dissolved in 35mL deionized water, and then 20mL formic acid was added. After magnetic stirring at room temperature for 60min, the mixture was transferred to a 100mL polytetrafluoroethylene reactor and hydroheated at 220℃ for 18h. After naturally cooling to room temperature, the mixture was filtered and washed with anhydrous ethanol and deionized water for many times. The obtained solid was dried in an oven at 70℃ for 12h to synthesize WS2 / Ni-SBA-15.
[0103] 5% H2, 30ppm CS2, and N2 were used as carrier gases to simulate blast furnace gas. The total flow rate was controlled at 200mL / min and the reaction space velocity was 40000h -1 , the ultraviolet light intensity is 9W, the relative humidity is 6.5%, 0.2g of the prepared catalyst material is placed in a photothermal catalytic reactor, and the catalyst is used to synergistically convert CS2 in blast furnace gas by photothermal reaction.
[0104] The catalyst performance was tested at 200°C. The CS2 conversion rate of the WS2 / Ni-SBA-15 catalyst was 60% under only hot catalyst and 75% after adding ultraviolet light. The H2S selectivity was 70% under only hot catalyst and 85% after adding ultraviolet light.
[0105] The composition and crystallinity of the catalyst were characterized by XRD. Figure 1 XRD patterns of the prepared catalysts show that the diffraction peaks of all samples include the (002) and (100) crystal planes of WS2 and the (200) crystal plane of WO3, while the (010) crystal plane of Ni3S2 only exists in the catalyst doped with Ni. After Ni is doped on the catalyst support, the peak intensity of WS2 becomes significantly larger, while the peak intensity of WO3 becomes weaker. After Ni doping, as the hydrothermal temperature increases, the peak intensity of WO3 gradually weakens, the peak intensity of WS2 first increases and then weakens, and the peak intensity of Ni3S2 gradually increases.
[0106] The synthesized catalysts were analyzed using X-ray photoelectron spectroscopy (XPS) to characterize the chemical composition and valence states of the elements present. Figure 2 (a) is the S2p XPS spectrum of the prepared catalyst material. In the S2p orbital, 162.0eV to 163.4eV, the two peaks belong to the SW bond. Because of the Ni doping, the peak of the S2p orbital is shifted. At 220℃, after Ni doping, the peak intensities of W and S will increase, indicating that more WS2 is formed on the surface of the catalyst, and WO3 is formed. Figure 2 (b) is the W 4f XPS spectrum of the prepared catalyst material. The two peaks at 35.6 eV to 38.2 eV in the W 4f orbital correspond to the WO bond, indicating that WO3 exists on the surface of the sample during the preparation process, which belongs to W 6 + , 32.5eV~34.8eV, the two peaks correspond to the WS bond, indicating that the synthesized catalyst is W 4+ WS2.
[0107] SEM was used to further evaluate the surface morphology and chemical content of the prepared catalysts. Scanning SEM and EDS elemental images further revealed the distribution of Si, Al, O, Ni, W and S elements in the catalyst structures of WS2 / ZSM-5, WS2 / Ni-ZSM-5 (160°C), WS2 / Ni-ZSM-5 (220°C), and WS2 / Ni-ZSM-5 (240°C). The energy spectrum can clearly show the main distribution of O, Si, W and S elements on the catalyst surface. Figure 3 (g) and (c), it can be seen that after adding Ni, the flake-stacked spherical WS2 is more regular and the surface is smoother. Figure 3 (a), (c) and (e), it can be seen that with the increase of hydrothermal temperature, the spherical WS2 formed is more regular, but when the hydrothermal temperature is 240℃, the regular sphere begins to peel off and form flakes; at 220℃ and 240℃, in addition to the spherical WS2, there are also SiO2 rods. This shows that the hydrothermal temperature has reached the point where the ZSM-5 framework collapses, and the elements in the ZSM-5 framework will reorganize at high temperatures. The Si element will reorganize with the oxygen element in the catalyst into SiO2 and be independently distributed around the synthetic catalyst. The detached framework Al will interact with the doped Ni. The flake-stacked spherical WS2 formed at 220℃ can not only maintain a complete structure, but also partially collapse the ZSM-5 molecular sieve framework, and the doped Ni will interact with the Al element in the ZSM-5 molecular sieve framework, which is beneficial to the hydrogenation conversion and removal of organic sulfur.
[0108] XRD analysis has been performed to confirm the crystal structure of the synthesized material. It is known that doping Ni on the catalyst support does not change its original crystal structure, but only adds new lattice parameters to the original crystal structure. Figure 4 (h) and (d), it can be seen that after doping Ni on the catalyst support, the lattice spacing of WS2 and WO3 formed has no effect. Figure 4 (a), (c) and (e), it can be seen that after Ni doping, with the increase of hydrothermal temperature, in addition to WS2 and WO3 lattice fringes, Ni2S3 lattice fringes also appear. After Ni doping on the catalyst support, the WO3 lattice fringes of the catalyst synthesized at 160℃ are more, the WS2 lattice fringes of the catalyst synthesized at 220℃ are more, and the Ni2S3 lattice fringes of the catalyst synthesized at 240℃ are more. In the TEM image, it can be seen that there are many defects and distortions on the basal surface and edges.
[0109] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a Ni-doped defective WS2 catalyst, characterized in that: The following steps are involved: S11. dissolving the molecular sieve, nickel salt, tungstate, sulfiding agent, inorganic hydroxylamine hydrochloride and organic modifier in deionized water, adding a certain amount of organic acid, and subjecting to hydrothermal reaction for a certain period of time; S12. After the reaction was completed, the product was cooled to room temperature, filtered, washed with deionized water and anhydrous ethanol several times, and dried to obtain a solid product; S13. The solid product is placed in a photothermal catalytic reactor and reduced with 2% to 10% H2 at 300°C to 350°C to obtain a Ni-doped defective WS2 catalyst.
2. The method for preparing a Ni-doped defective WS2 catalyst according to claim 1, characterized in that: In S11, the molecular sieve is selected from ZSM-5, SBA-15, KIT-6, and MCM-41; The nickel salt is selected from nickel nitrate, nickel sulfate, and nickel hydroxide; The tungstate is selected from ammonium metatungstate and sodium tungstate; The vulcanizing agent is selected from thiourea and thioacetamide; The inorganic hydroxylamine hydrochloride is selected from hydroxylamine hydrochloride and N,O-dimethylhydroxylamine hydrochloride; The organic modifier is selected from hexadecyltrimethylammonium bromide and ascorbic acid; The organic acid is selected from formic acid, acetic acid, sulfuric acid and phosphoric acid.
3. The method for preparing a Ni-doped defective WS2 catalyst according to claim 2, characterized in that: The mass ratio of the molecular sieve: nickel salt: tungstate: sulfiding agent: inorganic hydroxylamine hydrochloride: organic modifier is (0.1-1):(1-2):(1-2):(1-2):(1-2):(1-2):(1-2); The solid-liquid ratio of the molecular sieve to deionized water is 1 / 200 to 1 / 50, and the solid-liquid ratio of the molecular sieve to the organic acid is 0.0082 to 0.0273.
4. The method for preparing a Ni-doped defective WS2 catalyst according to claim 1, characterized in that: In S11, the temperature of the hydrothermal reaction is 160° C. to 240° C., and the time is 7 h to 24 h.
5. An application of a Ni-doped defective WS2 catalyst, characterized in that: The following steps are involved: In a photothermal catalytic reactor, a certain amount of Ni-doped defective WS2 catalyst prepared by any of the methods described in claims 1 to 4 was taken, and the flow rate was 200 mL / min and the reaction space velocity was 30000-40000 h -1 , blast furnace gas with ultraviolet light intensity of 7 to 10W is subjected to photothermal synergistic hydrogenation conversion at 120℃ to 200℃ to obtain H2S; The H2S is then removed through adsorption purification.
6. The use of a Ni-doped defective WS2 catalyst according to claim 5, characterized in that: The amount of the Ni-doped defective WS2 catalyst used is 0.2 g.
7. A method for recycling Ni-doped defective WS2 catalyst, characterized in that: The specific steps are: The Ni-doped defective WS2 catalyst whose desulfurization efficiency decreases after application as described in any one of claims 5-6 is regenerated under a high temperature and high pressure hydrogen atmosphere.
8. The method for recycling a Ni-doped defective WS2 catalyst according to claim 7, characterized in that: The regeneration conditions are as follows: introducing 2% to 5% hydrogen at 320° C. to 470° C., 1.6 to 9.8 MPa and a flow rate of 20 to 80 mL / min, using N2 as a protective gas, and reacting for 12 to 36 hours.
9. A method for resource utilization of waste hydrodesulfurization catalyst, characterized in that: The specific steps are as follows: S21. The Ni-doped defective WS2 catalyst which has failed after the recycling method according to any one of claims 7-8 is calcined in an air atmosphere at 500°C to 800°C for 3h to 6h; S22. Take an inorganic acid aqueous solution with a concentration of 0.1 mol / L to 3.0 mol / L, and ultrasonically immerse the failed Ni-doped defective WS2 catalyst at a solid-liquid ratio of 15:1 to 10:1 at 50°C to 100°C for 30 to 60 minutes, and filter and separate the residue and the filtrate; S23. A quaternary ammonium salt solution was added to the filtrate at a concentration of 0.5 mol / L ~ 2.0 mol / L, kerosene was added to the total reaction solution by volume 60% ~ 65%, and n-decanol was added to the total reaction solution by volume 5% ~ 7.5%; The ratio of the aqueous phase to the organic phase is 1:1 to 1:2, and a tungsten-containing extract and a nickel-containing extract are obtained; S24. Adding NH4OH or NaOH aqueous solution to the tungsten-containing extract, stirring on an electromagnetic stirrer at 80°C to 100°C until dry to obtain an ammonium tungstate or sodium tungstate compound having a purity greater than 99%; H2C2O4 or H2SO4 or HCl solution is added to the nickel-containing extract as a precipitant, and precipitation recovery is carried out in an environment of 40°C to 60°C to obtain nickel oxalate, nickel sulfate or nickel chloride with a purity greater than 98%.
10. The method for resource utilization of a waste hydrodesulfurization catalyst according to claim 9, characterized in that: In step S24, the concentration of the NH4OH or NaOH aqueous solution is 0.1 mol / L to 1.0 mol / L, and the molar ratio of the hydroxide ion to the tungstate ion is 1:1 to 1:3; The concentration of the H2C2O4 or H2SO4 or HCl solution is 0.1 mol / L to 1.0 mol / L, the molar ratio of the oxalate to the nickel ion is 1:1 to 1:2, the molar ratio of the sulfate to the nickel ion is 1:1 to 1:3, and the molar ratio of the chloride ion to the nickel ion is 3:1 to 2:1.
Citation Information
Patent Citations
Treating method for vulcanized hydrogenation catalyst
CN104588043A
Hydrodesulfurization catalyst as well as preparation method and application thereof
CN119158616A
Dewaxing catalysts
US20140274664A1
A multifunctional catalyst and its composition for single step conversion of triglycerides to transportation fuels
WO2022162680A1